2004
DOI: 10.1021/es034424f
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of Mercury Methylation in an Experimental Reservoir

Abstract: For the past 9 years, we experimentally flooded a wetland complex (peatland surrounding an open water pond) at the Experimental Lakes Area (ELA), northwestern Ontario, Canada, to examine the biogeochemical cycling of methyl mercury (MeHg) in reservoirs. Using input-output budgets, we found that prior to flooding, the wetland complex was a net source of approximately 1.7 mg MeHg ha(-1) yr(-1) to downstream ecosystems. In the first year of flooding, net yields of MeHg from the reservoir increased 40-fold to appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
114
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(129 citation statements)
references
References 36 publications
13
114
2
Order By: Relevance
“…Research in the Experimental Lakes Area of Canada showed a 40-fold increase in aqueous MeHg concentrations following large-scale flooding and increased biological concentrations that persisted for more than a decade (4,14,15). Here we discuss the magnitude of potential changes driven by hydroelectric development compared with future climate-driven effects.…”
Section: Significancementioning
confidence: 96%
See 1 more Smart Citation
“…Research in the Experimental Lakes Area of Canada showed a 40-fold increase in aqueous MeHg concentrations following large-scale flooding and increased biological concentrations that persisted for more than a decade (4,14,15). Here we discuss the magnitude of potential changes driven by hydroelectric development compared with future climate-driven effects.…”
Section: Significancementioning
confidence: 96%
“…Flooding associated with reservoirs causes a long-term increase in MeHg production resulting from decomposing organic matter and changes in the geochemical environment that stimulate methylating bacteria (4,14,15). With increasing demand for renewable energy,…”
mentioning
confidence: 99%
“…Methylation has been extensively studied in boreal lakes and wetlands (Beijer and Jernelov 1979;Regnell 1994;Matilainen and Verta 1995;Pak and Bartha 1998;Benoit et al 2002;Eckley and Hintelmann 2006), notably at the Experimental Lakes Area in northwestern Ontario, where much of the early work surrounding factors influencing methylation was done (Furutani and Rudd 1980;Ramlal et al 1986Ramlal et al , 1993Miskimmin et al 1992;Kelly et al 1997;St. Louis et al 2004;Harris et al 2007).…”
Section: Wetlands and Sedimentsmentioning
confidence: 99%
“…The latter process leads to the release of Hg (e.g. see Klaminder et al [36] ) as well as the creation of MeHg (St. Louis et al [37] ). In particular, recently deposited Hg may be more susceptible to release and uptake by freshwater fish.…”
Section: Transformation and Delivery Of Hg From Terrestrial And Freshmentioning
confidence: 99%